Estudios experimentales en larvas de Bufo fernandezae Gallardo : Crecimiento longitudinal y su relación con el alimento, concentración de oxígeno y densidad (Amphibia: anura) - Kehr, Arturo Ignacio (1985)
The objective of this work is to analyze individual and combined effects of biotic and abiotic factors of the length growth of inmature stages of B. fernandezae Gallardo. The research was carried on under specified and constant laboratory conditions. The obtained results showed that the density was the main controlling factor upon the individual growth, being less important, in this sense, the alimentary offer arranged during the temporal extension of the experiments. Besides, no differences were detected between the reared spawns, under different disolved oxygen registered values. Furthermore, it is remarkable food abundance and accesibility influence on the successful development of the studied individuals.